2020
DOI: 10.1002/jcph.1757
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Voxelotor in Patients With Renal and Hepatic Impairment

Abstract: Two open-label studies assessed the safety, tolerability, and pharmacokinetics of Oxbryta (voxelotor) in subjects with hepatic or renal impairment. Eight subjects with severe renal impairment (estimated glomerular filtration rate <30 mL/min/1.73 m 2) and 8 healthy age-, sex-, and body mass index-matched controls were administered a single oral dose of voxelotor 900 mg. Seven patients with mild (Child-Pugh A), moderate (Child-Pugh B), and severe (Child-Pugh C) hepatic impairment and healthy age-, sex-, and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Voxelotor PK in plasma and whole blood were not significantly impacted by renal impairment in this analysis, which is consistent with the results of a previously published study 22 in which only minor effects of severe renal impairment (eGFR <30 ml/min/1.73 m 2 ) on voxelotor exposure were observed compared with controls, suggesting that dose adjustment is not warranted in this patient population. In contrast, voxelotor exposure was ~ 90% higher in patients with severe hepatic impairment (Child‐Pugh C) compared with controls, and a lower voxelotor dose (1000 mg) is recommended in this patient population in the approved prescribing information 22 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Voxelotor PK in plasma and whole blood were not significantly impacted by renal impairment in this analysis, which is consistent with the results of a previously published study 22 in which only minor effects of severe renal impairment (eGFR <30 ml/min/1.73 m 2 ) on voxelotor exposure were observed compared with controls, suggesting that dose adjustment is not warranted in this patient population. In contrast, voxelotor exposure was ~ 90% higher in patients with severe hepatic impairment (Child‐Pugh C) compared with controls, and a lower voxelotor dose (1000 mg) is recommended in this patient population in the approved prescribing information 22 …”
Section: Discussionsupporting
confidence: 91%
“…In contrast, voxelotor exposure was ~ 90% higher in patients with severe hepatic impairment (Child-Pugh C) compared with controls, and a lower voxelotor dose (1000 mg) is recommended in this patient population in the approved prescribing information. 22 In conclusion, these analyses demonstrated that voxelotor PK in both plasma and whole blood can be adequately described using a joint model. Mean exposures and percent Hb occupancy were greater with voxelotor 1500 versus 900 mg q.d.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There was no apparent effect of renal function on the excretion of voxelotor based on comparable half-life (t 1/2 ) values between subjects with severe renal impairment and healthy controls, and these results indicate that no dose adjustment is needed for patients with impaired renal function, and renal function was shown to have minor effects on voxelotor exposure, since excretion of the drug is mainly nonrenal. 8 However, it is important to note that voxelotor has not been evaluated in patients with end-stage renal disease requiring dialysis.…”
mentioning
confidence: 99%
“…Impaired renal function is a relatively frequent and sometimes serious complication in patients with SCD, and Preston et al 8 evaluated the safety, tolerability, and PK of voxelotor in subjects with various degrees of renal insufficiency. Eight subjects with severe renal impairment (eGFR <30 ml/min/1.73 m 2 ) and eight healthy matched controls were administered a single oral dose of voxelotor 900 mg.…”
mentioning
confidence: 99%